2016
DOI: 10.7745/kjssf.2016.49.5.531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Legume Cover Crops and Nitrogen Fertilization Rates on Yield and Nitrogen Use Efficiency of Waxy Corn (Zea mays L.) in No-Tillage System

Abstract: The adoption of legume cover crops in no-tillage system can contribute to improve soil fertility by providing several benefits, including reduction in soil erosion, suppression of weed growth and N supply to subsequent crops. We conducted a field study to investigate the effect of cover crops and nitrogen fertilization rates on yield and nitrogen use efficiency of waxy corn (Zea mays L.) in no-tillage upland field. Two legume cover crops, hairy vetch (Vicia villosa Roth) and crimson clover (Trifolium incarnutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Vetch was very successful in agriculture lands such as Choi and Daimon (2008) found as green manure to recover N in the sorghum crops. Ren et al (2019), Barbosa et al (2009) and Choi et al (2016) also found a positive effect of vetch to increase the use of water efficiency and to control the soil losses in agriculture land. This fully agrees with our study, which considered that is a good option for farmers that wish to achieve sustainable agriculture as to reduce the soil losses as the key target.…”
Section: Contrasted Soil Erosion Processes Under Plant Cover and Barementioning
confidence: 88%
“…Vetch was very successful in agriculture lands such as Choi and Daimon (2008) found as green manure to recover N in the sorghum crops. Ren et al (2019), Barbosa et al (2009) and Choi et al (2016) also found a positive effect of vetch to increase the use of water efficiency and to control the soil losses in agriculture land. This fully agrees with our study, which considered that is a good option for farmers that wish to achieve sustainable agriculture as to reduce the soil losses as the key target.…”
Section: Contrasted Soil Erosion Processes Under Plant Cover and Barementioning
confidence: 88%
“…Agricultural areas are among the most vulnerable territories and are affected by soil and water loss [1][2][3][4], pollution [5][6][7] and loss of fertility [8][9][10] and biodiversity [11][12][13]. This is especially noticeable in vineyards, where land degradation processes threaten the sustainability and quality of the final product [14][15][16].…”
Section: Introductionmentioning
confidence: 99%